The Integration of AI Technology in Students’ Academic Writing Process (Universitas Terbuka, 2025)
This research explores using artificial intelligence (AI) tools such as ChatGPT in scientific papers by students in Indonesia. The main focus of the study is on students' perceptions of ethical aspects, the risk of plagiarism, the limitations of technology, and its impact on the interaction between writers and tutors. This research uses a quantitative-descriptive approach, the data collection method done by distributing surveys. There were 112 respondents from various universities in Indonesia. The study was conducted to look at data on the use of AI in writing scientific papers. The questionnaire contains questions about the tendency to use AI in writing scientific papers, ethical considerations, the risk of plagiarism, the limitations of technology, and the impact of AI on interaction with tutors. The survey results showed that most respondents (62%) chose not to use ChatGPT to write scientific papers, while the other 38% chose ChatGPT. (84%) respondents scored four or higher on the dimension of ethical considerations. It indicates that a majority agreed or strongly agreed with the moral considerations when using ChatGPT to write a scientific paper. Regarding plagiarism, most respondents (74%) gave a four or greater score, indicating that most respondents agree or firmly agree that using a charge for writing scientific works poses a risk of plagiarism. For the ChatGp dimension of limitations, the vast majority (49%) gave neutral answers to the ChatGp language model dimension to understand and present information that matches the specific domain of the scientific work. Most students (46,01%) agree strongly on the differences in interaction with tutors in using ChatGPT for writing scientific articles. The findings of this study reveal that while AI, like ChatGPT , can improve efficiency in writing scientific papers, clear ethical guidelines are required. The risk of plagiarism and using information without listing the source is a significant concern. Moreover, the limitations of ChatGPT in understanding specific contexts must be acknowledged and overcome. The impact of ChatGPT on the interaction between authors and tutors also requires special attention, as it can affect the quality of academic guidance. Conclusion: This research affirms the importance of understanding and managing the challenges posed by using ChatGPT in writing scientific papers. Ethics, plagiarism, and technological constraints are issues to be considered. Clear guidelines and stricter policies are needed to ensure that ChatGPT supports do not harm academic integrity.